DETEKSI PEWAKTUAN MANAJEMEN LABA MELALUI AKTIVITAS RIEL DAN KAITANNYA DENGAN PERSISTENSI LABA - Nining Ika Wahyuni (Universitas Jember, 2013)
By analyzing the quarterly financial report, this research aims to provide empirical evidence about the timing of earnings management activities based riels (activities-based real earnings management) and profits related to alignment and the persistence of profits. Hypothesis are: (1) riels earnings management more done in the fourth quarter, (2) flattening profits through earnings management riel a positive impact on the persistence of earnings and (3) companies that allegedly made a profit through the manipulation of leveling riel activity has the persistence of profit higher in the fourth quarter than in any other quarter. This study tested three earnings management proxy riel operating cash flow is abnormal, abnormal discretionary expenses, and abnormal production boarding. Riel profit management is calculated by summing the three standardized proxy. The number of companies that serve as a sample according to the criteria is a company with 63 research period from 2004 to 2008. Of this amount, the company entered into a profit-based criteria grader Eckel model is as much as 26 companies. The collection of data with purposive sampling method. Testing the first and third hypothesis was tested with different test or indendent sample t-test while the second hypothesis was tested with regression. The first hypothesis test results showed that the average abnormal operating cash flow, abnormal discretionary expenses, and lodging in the abnormal production of the fourth quarter is statistically greater than in any other quarter. Standardize the amount of the three proxy in the fourth quarter is also statistically greater than in any other quarter. This study failed to support the second hypothesis which states that the flattening of profit through the manipulation of positive affect riel activity against the persistence of profits. In contrast, this study proves that the act of leveling a profit through the manipulation of riels activities negatively affect the persistence of profits. The third hypothesis test results show that the average difference between the persistence of profits in the fourth quarter with the other quarter was not statistically significant. So that it can be said that there is no difference in the persistence of profits in the fourth quarter with another quarter. Keywords: Activities-Based Real Earnings Management, Quarterly Financial Report.